COVID-19 mRNA-1273 vaccination induced mast cell activation with strongly elevated Th2 cytokines in a systemic mastocytosis patient - Weiss-Tessbach, Matthias; Haider, Teresa; Gowran, Aoife; Schubert, Lorenz; Mühlbacher, Jakob; Brankovic, Jelena; Wahrmann, Markus; Jilma, Bernd; Boehm, Thomas (Inflammation research, 2025)
Objective and design SARS-CoV-2 vaccines are recommended for mastocytosis patients. We describe clinical symptoms, chemokine, cytokine, metabolomic and lipidomic derangements in a systemic mastocytosis patient following mRNA-1273 booster vaccination. Methods Twenty-eight chemokines and cytokines, 41 amino acids and 16 lipid classes were quantified with state-of-the-art methods. Results Mast cell activation (MCA) symptoms started 24 h after the mRNA-1273 booster vaccination with significant metabolic, lipidomic and cytokine derangements. Histamine concentrations peaked at life-threatening 18 ng/ml concomitant with high tryptase. Peak plasma IL-1Ra, IL-5, IL-6, IL-10, IL-11, CXCL10 and GM-CSF concentrations were elevated 54-, 4.9-, 85-, 54-, 6.1-, 19- and 6.4-fold respectively. Tocilizumab, an IL-6 receptor antagonist, was administered 6 h after admission, because of the highly elevated IL-6 concentrations. More than one year later IL-6 was highly elevated during another MCA attack likely caused by a PCR-proven SARS-CoV-2 infection and tocilizumab was again used. Clinical symptoms improved during the following 12 h similar to the vaccine booster MCA attack. Conclusions A mRNA-1273 first booster vaccination likely caused a delayed severe MCA attack with highly elevated Th 2 -biased cytokines with metabolic and lipidomic derangements. Administration of an IL-6 receptor blocker during both MCA attacks might have shortened the duration of clinical symptoms.